2022
DOI: 10.1029/2022jc018518
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Cycle of Sea Surface Salinity in the Angola Upwelling System

Abstract: The Angolan upwelling region is a very productive marine ecosystem in the southeast Atlantic and serves as the gateway for connecting the equatorial dynamics to the northern Benguela. Fisheries are widely developed along the Angolan shore and are critical for economic security and the employment of local coastal communities (Hutchings et al., 2009;Sowman & Cardoso, 2010). Contrary to the Benguela upwelling system that is sustained by high alongshore upwelling favorable winds (Carr & Kearns, 2003), the highly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 44 publications
3
23
2
Order By: Relevance
“…Seemingly contradicting to our results, the study of Awo et al (2022) showed that mean horizontal advection is an important term for the seasonal salinity budget. Their analysis shows that freshwater from the Congo River can reach 11°S by meridional advection in February/March and in October/November.…”
Section: Summary and Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Seemingly contradicting to our results, the study of Awo et al (2022) showed that mean horizontal advection is an important term for the seasonal salinity budget. Their analysis shows that freshwater from the Congo River can reach 11°S by meridional advection in February/March and in October/November.…”
Section: Summary and Discussioncontrasting
confidence: 99%
“…However, as the meridional temperature gradient is weak in that region, the mean horizontal advection is not important for the local ML heat budget. Thus, the results of our study do not oppose the results found by Awo et al (2022).…”
Section: Summary and Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…4). In the tAUS during austral winter, maximum productivity is observed at the same time as the lowest SST and the strongest cross-shore temperature gradient are present (Awo et al 2022;Körner et al 2022;Tchipalanga et al 2018). In contrast to other eastern boundary upwelling systems, the seasonality of the productivity in the tAUS cannot be explained by local wind forcing (Ostrowski et al 2009).…”
Section: Tropical Angolan Upwellingmentioning
confidence: 89%